ASSESSMENT OF RENAL DYSFUNCTION AND COMORBID CONDITIONS IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE - Shoira Gulimboyevna Matrzaeva (Web of Journals Publishing, 2025)
Chronic kidney disease (CKD) is a frequent but under-recognized comorbidity in severe chronic obstructive pulmonary disease (COPD). We aimed to determine the prevalence of renal dysfunction and its association with comorbid conditions in patients hospitalized with severe COPD.
Keywords: COPD, chronic kidney disease, glomerular filtration rate, comorbidity, cardio-renal syndrome.